2006
DOI: 10.1017/s0031182006000369
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transmissibility ofTrypanosoma congolensestrains, isolated in a trypanosomiasis endemic area of eastern Zambia, byGlossina morsitans morsitans

Abstract: Transmission experiments were conducted to compare the transmissibility of genetically different Trypanosoma congolense (Savannah subgroup) strains isolated from cattle in a trypanosomiasis endemic area of eastern Zambia. A total of 17 strains were compared. Three strains were extremely virulent with a short pre-patent period, high parasitaemia and a short median survival time (between 5 and 9 days) in mice. The remainder of the strains belonged to the moderate (6 strains) or low (8 strains) virulence categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
9
1
Order By: Relevance
“…In spite of this, both domestic and sylvatic trypanosome strains were found significantly better transmitted if they are more pathogenic to mice, even when the number of trypanosomes present in the blood meal is standardized. This observation is in agreement with the findings of Masumu et al(2006b). The parasite dose used in our study (50 trypanosomes/µl) was well above the dose we observed to cause a threshold (12.5 trypanosomes/µl), thus indicating that this difference was not due to parasite density as assumed by the simple trade-off model of Anderson and May (1982).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In spite of this, both domestic and sylvatic trypanosome strains were found significantly better transmitted if they are more pathogenic to mice, even when the number of trypanosomes present in the blood meal is standardized. This observation is in agreement with the findings of Masumu et al(2006b). The parasite dose used in our study (50 trypanosomes/µl) was well above the dose we observed to cause a threshold (12.5 trypanosomes/µl), thus indicating that this difference was not due to parasite density as assumed by the simple trade-off model of Anderson and May (1982).…”
Section: Discussionsupporting
confidence: 93%
“…A linear relationship was reported between the transmissibility of the parasite and the host parasitaemia at low parasite concentrations only (10 -3 to 5 trypanosomes/µl) (Walshe et al, 2011). Moreover, for the same level of parasitaemia in mice, more pathogenic strains are more transmissible to tsetse flies (Masumu et al, 2006b). Hence the question: in a domestic environment how effective is the transmission of T. congolense to tsetse flies compared to trypanosomes cycling in a sylvatic environment if domestic strains present a lower pathogenicity and a lower proliferation capacity?…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, previous studies have shown that this species is composed of subspecies differing at genetic (Gashumba et al, 1988; Knwoles et al, 1988; Young and Godfrey, 1983) and biological (Bengaly et al, 2002; Reifenberg et al, 1997) level. Furthermore, trypanosome isolates belonging to the same subspecies and circulating in a restricted area have been found to differ in virulence (Masumu et al, 2006a), transmissibility (Masumu et al, 2006b) and antigenicity (Frame et al, 1990; Masake et al, 1987). Such differences were thought to influence the outcome of the disease in different areas.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cholera pandemics are associated with a limited diversity of related, highly transmissible Vibrio cholerae strains (4). For vectorborne pathogens, efficient transmission is also dictated by infection and replication within the arthropod host (10,15,25,26). While the basic cycle of development within the arthropod vector has been identified for many important pathogens, including Anaplasma, Borrelia, Plasmodium, Rickettsia, and Trypanosoma, the critical microbial determinants of transmission efficiency in the vector remain unknown for most bacterial and protozoan pathogens.…”
mentioning
confidence: 99%